Indirect effects of COVID-19 on maternal and child health in South Africa. Issue 1 (31st December 2023) - Thsehla, Evelyn; Balusik, Adam; Boachie, Micheal Kofi; Tombe-Mdewa, Winfrida; Kabudula, Chodziwadziwa; Du Toit, Jacques; Kahn, Kathleen; Gómez-Olivé, Francesc Xavier; Tollman, Stephen; Goldstein, Susan; Hofman, Karen
ABSTRACT: Background: The unfinished burden of poor maternal and child health contributes to the quadruple burden of disease in South Africa with the direct and indirect effects of the COVID-19 pandemic yet to be fully documented. Objective: To investigate the indirect effects of COVID-19 on maternal and child health in different geographical regions and relative wealth quintiles. Methods: We estimated the effects of COVID-19 on maternal and child health from April 2020 to June 2021. We estimated this by calculating mean changes across facilities, relative wealth index (RWI) quintiles, geographical areas and provinces. To account for confounding by underlying seasonal or linear trends, we subsequently fitted a segmented fixed effect panel model. Results: A total of 4956 public sector facilities were included in the analysis. Between April and September 2020, full immunisation and first dose of measles declined by 6.99% and 2.44%, respectively. In the follow-up months, measles first dose increased by 4.88% while full immunisation remained negative (−0.65%) especially in poorer quintiles. At facility level, the mean change in incidence and mortality due to pneumonia, diarrhoea and severe acute malnutrition was negative. Change in first antenatal visits, delivery by 15–19-year olds, delivery by C-section and maternal mortality was positive but not significant. Conclusion: COVID-19 disrupted utilisation of child health services. While reduction in child health services at the start of the pandemic was followed by an increase in subsequent months, the recovery was not uniform across different quintiles and geographical areas. This study highlights the disproportionate impact of the pandemic and the need for targeted interventions to improve utilisation of health services.